The Role of Learning Bridges Program in Linking Knowledge to life from Science teacher perspective in Jerash Governorate - Altwaisi, Ahmad Mohammed Ahmed (Journal of Educational and Psychological Sciences, 2022)
This study aimed to identify the Role of learning bridges program in linking knowledge to life from science teacher's perspective in Jerash governorate. To achieve the objectives of the study, the study used the descriptive quantitative analytical approach, the sample of study consisted from (175) female and male Science teacher, and a questionnaire for data collection; it consisted of (30) statements. The results indicated that the Role of learning bridges program in linking knowledge to life from science teacher's perspective in Jerash governorate was High with average (4.05 out of 5), and it had apossitive effect in linking knowledge to life, the result also showed there were no statistical significant differences at (α ≤ 0.05) in the variable of teacher sex. According to the result the study recommended the need to pay attention to life skills and the procedures and methods of teaching them.
Keywords: Learning Bridges Program; Linking Knowledge to life; Science teacher; Jerash Governorate